THE USE OF EUPHEMISM IN RISHI SUNAK’S FIRST SPEECH AS UK PRIME MINISTER - Isti Ramona Lubis (Universitas Negeri Medan, 2023)
This qualitative study delves into the use of euphemism in Rishi Sunak's inaugural speech as UK Prime Minister, specifically examining the types and functions of euphemisms in political discourse. By conducting a linguistic analysis of the speech delivered outside Number 10 Downing Street in London on October 25, 2022, a range of euphemistic expressions such as metonymy, substitution, dysphemism, acronym/abbreviation, and synecdoche were identified. The research highlights the strategic deployment of euphemisms to convey sensitive or unpleasant ideas in a socially acceptable manner, showcasing their pivotal role in shaping discourse and managing perceptions. Through an exploration of the nuanced nature of euphemisms in political communication, this study contributes to a deeper understanding of how language is wielded to uphold integrity and professionalism in public speaking. By examining euphemisms in different cultural contexts and their impact on communication, this research contributes to a deeper understanding of the evolution and influence of euphemisms. The findings underscore the significance of euphemistic language in political contexts, offering valuable insights into the complexities of language use, sociolinguistics, and semantics. Overall, this analysis provides meaningful implications for language learners, researchers, and individuals interested in unraveling the intricacies of political rhetoric and communication strategies within the realm of public discourse. The findings underscore the importance of studying euphemisms in political discourse, international diplomacy, and formal speeches, showcasing their role in conveying positive connotations, neutralizing unpleasant words, and maintaining formal decorum.